The Gastropod Genus Xenuroturris (Iredale,1929) Evaluated and a New Turrid Lophiotoma Olangoensis, Described from the Central Philippines - Olivera, Baldomero M. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 14 No 2 (2002))
none
Keywords: venomous snail, toxoglossate gastropod, Conacea, molluscan taxonomy, Turridae